2011
DOI: 10.1016/j.vetpar.2011.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of potentially zoonotic Giardia duodenalis from exotic and wild animals kept in captivity in Brazil

Abstract: We have studied the variability of glutamate dehydrogenase (gdh) and small subunit ribosomal (SSU) rRNA coding genes of Giardia species in fecal samples isolated from wild and exotic animals in Brazil, and compared with homologous sequences of isolates from human and domestic animals characterized in previous studies. Cysts of Giardia duodenalis were obtained from feces of naturally infected monkeys (Alouatta fusca) (n=20), chinchillas (Chinchilla lanigera) (n=3), ostriches (Struthio camelus) (n=2) and jaguar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 21 publications
4
19
0
1
Order By: Relevance
“…of Giardia duodenalis genotype . Giardia cysts found in one of the cougars (Puma concolor) in the present study were genotyped and were also of human origin (SOARES et al, 2011). In all these cases, epidemiological evidence suggests that human beings are the source of infection, through direct or indirect environmental contamination from raising domestic animals.…”
Section: Introductionsupporting
confidence: 48%
“…of Giardia duodenalis genotype . Giardia cysts found in one of the cougars (Puma concolor) in the present study were genotyped and were also of human origin (SOARES et al, 2011). In all these cases, epidemiological evidence suggests that human beings are the source of infection, through direct or indirect environmental contamination from raising domestic animals.…”
Section: Introductionsupporting
confidence: 48%
“…It has been reported that assemblages A and B are able to infect humans [56]. Interestingly, these assemblages have been reported from wild animals under conditions of captivity [57], and from cattle [58]. bLf, bLfcin, hLf and human Lfcin (hLfcin) showed a lytic effect on Giardia trophozoites.…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…Zoonotic genotypes A and/or B were reported in dogs, cats, non-human primates, cattle, sheep, exotic and wild animals in Brazil (Volotao et al 2007(Volotao et al , 2008(Volotao et al , 2011Souza et al 2007;Gomes et al 2011;Soares et al 2011;Paz e Silva et al 2012a,b;Fava et al 2013), suggesting the potential for environmental contamination and a risk for goat infection.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, studies on the molecular epidemiology of Giardia duodenalis are scarce, but the genotyping of isolates has been reported in dogs, cats, cows, sheep, non-human primates, and exotic and wild animals (Volotao et al 2007;Souza et al 2007;Volotao et al 2008;Volotao et al 2011, Gomes et al 2011Soares et al 2011;Paz e Silva et al 2012a; Paz e Silva et al 2012b;Fava et al 2013).…”
mentioning
confidence: 99%